ESCAPEMENT OF CARP HATCHLINGS FROM SHOOTING NETS - Ghosh, K K; Sinha, M; Srivastava, N K (Indian Journal of Fisheries, 2011)
The escapement of hatchlings was first suggested in a discussion on thevariation in catching efficiencies of shooting nets made of different meshed nettings(Anon., 1965). The shooting net is essentially a filtration net. The catch dependson the amount of water filtered by the net and on the retentivity of the hatchlingsflowing into it. The design of the shooting net is strikingly similar to the earliertwo-winged trawl net with the basic diffference that it has an open cod-end throughWhich the filtered-off live hatchlings pass to a wider receptacle at the end of the net.